Hubungan Self-Acceptance dengan Body Dissatisfaction pada Perempuan Emerging Adulthood Pengguna Instagram - Mariani, Pebri; Yasmin, Maya (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The aim of this study is to examine the relationship between self-acceptance and body dissatisfaction in female emerging adulthood Instagram users. This research was conducted with a correlational quantitative design. The study population consisted of 385 female emerging adulthood Instagram users in West Sumatra who were selected using an accidental sampling approach. The instrument used in this research was compiled by the researcher where body dissatisfaction is guided by the aspects expressed by Tariq & Ijaz (2015), then self-acceptance is guided by the aspects put forward by Powell (1989), each of which has a reliability of 0.917 and 0.859. Based on product moment analysis, it was found that the correlation value p = 0.00 (p < 0.05) and r = 0.553, which indicates that there is a significant negative relationship between variables. The result of this study is Ha accepted, which means that there is a negative relationship between self-acceptance and body dissatisfaction in female emerging adulthood Instagram users